The Relationship Between Interpersonal Communication and Futsal Athletes' Motivation to Compete - Mochammad Ramadhan Hadiansah; Mochamad Yamin Saputra; Mona Fiametta Febrianty (Universitas Negeri Semarang, 2025)
This study aims to determine the relationship between interpersonal communication and the motivation to compete in futsal athletes. This study uses a quantitative descriptive method with a correlational design. The population in the study were 29 members of the futsal extracurricular at the Modern Islamic Boarding School of Mathla'ul Huda, sampling using a total sampling technique. The instrument in the study used a questionnaire scale of interpersonal communication and a scale of motivation to compete which were arranged based on the indicators of each variable. Data were collected by distributing questionnaires to all respondents, then analyzed using the SPSS 23.0 program with the Pearson Product Moment correlation test. The results of the study showed a significant relationship between interpersonal communication and the motivation to compete in futsal athletes. The conclusion is that the more effective communication, whether through clear instructions, emotional support, or positive feedback, the higher the motivation of athletes in facing the match. This finding confirms that quality interpersonal communication plays a crucial role in increasing motivation, competitive spirit, and supporting the achievements of futsal athletes.